Alzheimer's disease: Newer biomarkers - Ankit Dangi (Wolters Kluwer Medknow Publications, 2021)
Fifty million people are affected with dementia worldwide with Alzheimer's disease (AD) accounting for 70%–80% of these cases. In India alone, 4.1 million people suffered from dementia in 2015. To date, there are no definitive treatment options for AD and the overall treatment gap in India stands at 90%. Attempts have been made to define AD biologically. This has been made possible due to advances in the identification of biomarkers that indicate the neuropathological changes responsible for AD. Identification of these biomarkers has implications for disease staging, prognostication, and identifying drug targets. Here, we summarize the advances in the field of biomarkers in AD.